Umbilical endometriosis: a case report and review of the literature - Fuentes, Huber Díaz; Quijano, Carlos de Jesús Cocom; Negrete, Christian Rodríguez (International Journal of Research in Medical Sciences, 2021)
Endometriosis is defined as the presence of endometrial glands and stroma outside the uterus. It affects 7-10% of women of reproductive age. Most commonly, the condition affects pelvic organs, however, 12% are encountered at extragenital sites, such as lungs, diaphragm, or umbilicus. Authors present the case of a 32 year old patient presenting with secondary umbilical endometriosis, after a recent surgical procedure. Manifesting umbilical mass, pain and catamenial bleeding from the umbilicus.